A critical review about metal organic framework-based composites: Potential applications and future perspective - Meskher, Hicham (Journal of Composites and Compounds, 2023)
The properties of metal-organic frameworks (MOFs), a potential class of porous crystalline materials with a wide range of uses, depend on their structural details, including compositions and architectural designs. Through functionalization and their interaction with other nanomaterials, MOFs' structure and design have undergone changes as a result of their extensive research. Numerous outstanding evaluations on single MOFs, MOF-based composites created through conjugation with non-MOF materials, and their derivatives have summarized the developments in the field of MOFs. A thorough examination of MOFs and their combination is, however, lacking. In this perspective, we present a current and thorough description of the accomplishments of MOF-based hybrids below. First, a description of the synthetic strategy/formation process is provided to illustrate how host and visitor MOFs interact. The structural diversity in MOF-based systems is then thoroughly examined to show how MOF systems enable advancements in abased composites for a variety of applications, particularly in the medical and environmental fields. Finally, we present our personal opinions on the difficulties and potential paths for the development of MOFs materials.